Associations of interleukin-1 (IL-1) gene variation and IL-1 receptor antagonist phenotypes with immunological responses, metabolic dysregulation and type 2 diabetes - Luotola, Kari, 1964- (Helsinki : University of Helsinki, 2011)
Tiivistelmä suomeksi.
Väitöskirja
Julkaistu myös painettuna.
World Wide Web.
Nimeke PDF-nimiösivulta.
968735
Keywords: interleukiinit; sytokiinit; diabetes; väitöskirjat